Effect of SGLT-2 inhibitor (remogliflozin) plus DPP4 inhibitor (vildagliptin) on diabetic nephropathy in patients with type 2 diabetes mellitus comparison with combination of metformin and sulphonylureas - Gupta, Vishal Kumar; Pannu, Deepak; Singh, Mahendra Pal; Kumar, Lalit (International Journal of Advances in Medicine, 2023)
Background: Diabetes is leading cause of renal failure in entire world. Approximately 20-40 percent of patients with diabetes develop diabetic nephropathy. Newer drugs like SGLT-2 inhibitors and DPP-4 inhibitors are valuable option for Diabetic Nephropathy. Remogliflozin etabonate (RE) is the latest addition to the SGLT2 inhibitor class of drugs that have been recently approved in India for the management of T2DM.This study was conducted to elaborate effect of SGLT2 inhibitor (remogliflozin) plus DPP4 inhibitor (vildagliptin) on diabetic nephropathy in patients of Type 2 DM. Methods: This hospital based, comparative, open label, randomized controlled trial has been carried out in our department during January 2020 to October 2022 on 60 patients. Group 1 was given metformin 500 mg BD and glimepiride 1 mg BD and group 2 was given FDC of remogliflozin 100 mg and vildagliptin 50 mg BD with 32 patients in group 1 and 28 patients in group 2. The study was approved by ethical committee of our institute. Results: Mean (SD) of urine ACR in metformin and glimepiride group at screening, 12 weeks, 24 weeks, and at 36 weeks were 93.64 (53.92), 95.56 (52.76), 89.96 (50.22) and 90.9 (53.56) respectively mean (SD) of urine ACR in remogliflozin and vildagliptin group at screening, 12 weeks, 24 weeks, and at 36 weeks were 108.28 (68.5), 100.73 (55.5), 99.35 (55.71) and 75.1 (38.7) respectively. Mean (SD) of eGFR in metformin and glimepiride group at screening, 12 weeks, 24 weeks, and at 36 weeks were 59.62 (18.57), 61.2 (11.1), 60.06 (14.37) and 60.8 (13.3) respectively. Mean (SD) of eGFR in remogliflozin and vildagliptin group at screening, 12 weeks, 24 weeks, and at 36 weeks were 68.03 (16.35), 65.8 (7.96), 66.28 (15.13) and 68.4 (11.6) respectively. Conclusions: Remogliflozin and vildagliptin combination has significant reduction of proteinuria and eGFR improvement when compared to metformin plus glimepiride.